Interference Management Using Distance-based Clustering Method for D2D Communication Underlaying Multicell Cellular Network - Sabella, Soraida; Susanto, Misfa; Setyawan, FX Arinto (Jurnal Elektronika dan Telekomunikasi, 2023)
Device-to-Device (D2D) communication is a technology candidate to support the next generation of cellular communication networks. D2D has the potential to boost the efficiency of frequency resources and system capacity. Generally, D2D performs in-band underlaying or shares frequency channels with traditional cellular users, which can cause co-channel interference problems between these two types of users. This paper offers a solution through a clustering technique for D2D users (DUEs) to reduce interference among DUEs. Clustering technique is performed on DUEs by allocating different frequency channels in a group, in order to reduce the interference effects experienced. Thus, it is expected that through this proposed method, both D2D and cellular users can experience better signal quality with minimal interference effects. Two systems have been considered i.e., the conventional/baseline system and the system with the proposed clustering method. The simulation results show that the SINR (Signal to Interference plus Noise Ratio) values and throughput for the proposed system compared to the baseline system has increased. The SINR result obtained is 16.8 dB for the baseline system and 17.68 dB for the proposed system, and resulting an improvement of 5.4%. Therefore, applying the proposed clustering method is able to increase acceptability of the desired signals for the observed DUEs. Then, the throughput value also increases by 5%, i.e., from 56.17 to 59 Mbps, which the system with the proposed clustering method provides a better increase in data transmission speed compared to the baseline system.